Psychoeducation: Prevention of gadget addiction through proper parenting in the digital era for society - Rizti Rahmat Purnamasari; Siti Muthia Dinni (Community Empowerment, 2025)
Gadgets are one form of technological, information, and communication advancement that has a significant impact on almost all aspects of life. The increase in gadget ownership and internet use occurs across almost all age ranges, including children and adolescents. The lack of understanding and awareness of parents can be a risk factor for children and adolescents experiencing gadget addiction. The intervention carried out is psychoeducation which aims to increase knowledge and raise public awareness regarding the importance of parenting in children and adolescents so that behavioral changes are formed so that children and adolescents can avoid gadget addiction. The methods used are: 1) interactive lectures; 2) video presentation; 3) discussion; 4) pre-test and post-test. Based on the analysis results, it was concluded that there was an increase in public understanding regarding the impact of gadget use and the importance of appropriate parenting to prevent gadget addiction before and after being given psychoeducation.